Universal HBV vaccination dramatically reduces the prevalence of HBV infection and incidence of hepatocellular carcinoma. Issue 5 (21st July 2022) - Wong, Grace Lai‐Hung; Hui, Vicki Wing‐Ki; Yip, Terry Cheuk‐Fung; Liang, Lilian Yan; Zhang, Xinrong; Tse, Yee‐Kit; Lai, Jimmy Che‐To; Chan, Henry Lik‐Yuen; Wong, Vincent Wai‐Sun
Summary: Background: Universal vaccination of newborns with hepatitis B virus (HBV) vaccine is the most important strategy to prevent chronic HBV infection and its complications of which hepatocellular carcinoma (HCC) as the deadliest. Aims: To evaluate the impact of universal HBV vaccination on the prevalence of chronic HBV infection, and the incidences of HCC and hepatic events in young adults born before and after the introduction of the universal HBV vaccination programme in 1988 in Hong Kong Methods: This was a territory‐wide retrospective observational cohort study of consecutive adult subjects born in 1970–2002 with hepatitis B surface antigen (HBsAg) checked. Subjects born during the vaccination era (1988–2002) were included in the vaccinated cohort; subjects born between 1970 and 1987 were included in the unvaccinated cohort. Results: We included 695, 925 subjects for HBV prevalence analysis. Chronic HBV infection dropped from 14.3% in subjects born in 1970, to 6.7% in subjects born in 1988. In total, 53, 960 vaccinated and 318, 290 unvaccinated subjects who had available clinical data were included for event analysis. HCC and hepatic events occurred in 44 (0.1%) and 75 (0.1%) of the vaccinated subjects and in 1305 (0.4%) and 1806 (0.6%) of the unvaccinated subjects, respectively. All incidence rates remained numerically lower in vaccinated subjects after adjustment for age, gender and antiviral treatment, but failed to reach statistical significance due to very low incidence rates. Conclusions: Universal HBV vaccination markedly reduces the prevalence of chronic HBV infection and may contribute to the decreased incidences of HCC and hepatic events. Abstract :